Preventing stunting increase: "Si Penting" program by UPI's community service in Karangwangi village - Susilo Aditya Darma; Reksa Alamsyah (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
This community service highlights the severe issue of stunting in Indonesia, notably after the country ranked second in Southeast Asia for the prevalence of toddlers experiencing poor growth in 2018. Stunting has become a primary focus of the Indonesian government. The University of Education Indonesia (UPI), as one of the leading institutions in the country, took the initiative to prevent the increase in stunting rates through the Thematic Real Work Lecture (KKN-T) program with the theme "Si Penting" (Mahasiswa Peduli Stunting). This community service explores the active role of UPI Si Penting KKN-T students in maintaining the Zero Stunting condition in Karangwangi Village. By forming various work programs focused on toddlers, adolescents, and pregnant women, students successfully made positive contributions through activities such as integrated health posts, counseling, awareness campaigns, the CEKAS program, POSBINDU-PTM, the realization of TP-PKK innovations, and the Ketapang Kancana program. The innovative steps taken by TP-PKK and the Karangwangi Village officials create a breakthrough in stunting prevention efforts while simultaneously enhancing the village's self-reliance. Thus, the KKN-T "Si Penting" activities provide a concrete solution for the community in Karangwangi Village and inspire improving health services, especially related to stunting, at the local level.   Abstrak Pengabdian pada masyarakat ini menyoroti masalah stunting yang menjadi perhatian serius di Indonesia, terutama setelah negara ini menduduki peringkat kedua di Asia Tenggara dalam prevalensi balita yang mengalami pertumbuhan buruk pada tahun 2018. Stunting menjadi fokus utama Pemerintahan Indonesia, dan Universitas Pendidikan Indonesia (UPI), sebagai salah satu institusi terkemuka di Indonesia, mengambil inisiatif untuk mencegah peningkatan angka stunting melalui program Kuliah Kerja Nyata Tematik (KKN-T) dengan tema "Si Penting" (Mahasiswa Peduli Stunting). Pengabdian ini dilaksanakan dalam KKN-T UPI Si Penting dalam mempertahankan kondisi Zero Stunting di Desa Karangwangi. Dengan membentuk berbagai program kerja yang difokuskan pada balita, remaja, dan ibu hamil, mahasiswa berhasil memberikan kontribusi positif melalui kegiatan posyandu, konseling, penyuluhan, program CEKAS, POSBINDU-PTM, realisasi inovasi TP-PKK, dan program Ketapang Kancana. Langkah inovatif TP-PKK dan aparat Desa Karangwangi menciptakan gebrakan baru dalam upaya pencegahan stunting, sambil meningkatkan kemandirian desa secara keseluruhan. Dengan demikian, kegiatan KKN-T "Si Penting" tidak hanya menjadi solusi konkret untuk masyarakat Desa Karangwangi tetapi juga memberikan inspirasi bagi peningkatan pelayanan kesehatan, terutama terkait stunting, di tingkat lokal. Kata Kunci: keterlibatan masyarakat, pengabdian kepada masyarakat, inovasi program kesehatan, pencegahan stunting